Academic Administration of School Administrators in Khlongsan District under the Bangkok Metropolitan Administration - สุแพง ทัศนียา; แก้วมงคล ทรงยศ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The purposes of this research were to: 1) examine the level of academic administration of school administrators under the Khlongsan District Office, Bangkok Metropolitan Administration; 2) compare academic administration as perceived by teachers, classified by gender, work experience, and school size; and 3) propose guidelines for improving academic administration. The sample consisted of 142 teachers under the Khlongsan District Office, selected based on the Krejcie and Morgan (1970) table using stratified random sampling and simple random sampling. The research instruments were a 5-point rating scale questionnaire and a semi-structured interview. The content validity ranged from 0.80 to 1, and the overall reliability coefficient was 0.892. Data were analyzed using percentage, mean, standard deviation, t-test, F-test, and content analysis. Pairwise comparisons were conducted using Scheffé’s method. The findings revealed that: • The overall and individual aspects of academic administration were at a high level. Instructional management had the highest mean, followed by internal supervision, while academic planning had the lowest mean. • There were no significant differences in overall opinions on academic administration when classified by gender, work experience, and school size. However, a statistically significant difference at the .05 level was found in curriculum development, while other aspects showed no significant differences. • The proposed guidelines for improving academic administration include: using empirical data and participatory approaches in academic planning; developing flexible and context-based curricula; promoting active and experiential learning while enhancing teacher capacity; applying diverse and authentic assessment methods; fostering professional learning communities (PLC) and collegial supervision; and supporting the use of digital technology and online learning resources to enhance innovative learning.